Bases of 15s rugby player´s physical training in Finland - Tyrväinen, H (2015)
This portfolio work is systematic literature review about physical demands 15 aside rugby and conditioning methods for it. These papers are included in appendices with simplified guide to laws and terminology of rugby union game. Papers are aimed to give aid for the advanced men´s 15 aside union rugby players and their coaches in Finland.